THE ROLE OF ACADEMIC STAFF IN THE EFFECTIVE GOVERNANCE IN THE UNIVERSITIES: EXPERIENCE OF FRANCE - Olga Palamarchuk (Borys Grinchenko Kyiv Metropolitan University, 2019)
This article is devoted to the analysis of the role of academic staff in the effective governance of the universities in France. Models of governance of the universities of France are analyzed. It is found that in France there is a dual (asymmetric) model of governance. It has been established that in an «asymmetric» dual structure, one of the governing bodies can be considered as the main decision-making body and the other body has more limited powers. The article analyzes the system of governance and the role of academic staff in such institutions of higher education as the University of Paris-Dofin, the Louis-Bachelier Institute, the Curie Institute, the University of Sorbonne. It is revealed that in general, the main governing bodies of the university are three central authorities: the Board of Directors, the Scientific Council and the Academic and Student Life Council. It has been established that all the governing bodies of universities in France include academic staff with a total of 8 to 13 people, depending on the Council to which they belong. It is analyzed that the main functions of academic staff are decision-making at the level of the governing bodies of the University, participation in discussions on financial, strategic issues, decision-making on student associations, student life, research questions, and teaching. It has been found that the activity of academic staff in the effective governance of the universities in France is advisory. It is noted that academic staff can be involved as an external expert in the decision-making process in other universities.